2020
DOI: 10.1155/2020/2867241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biomarkers HMGB1 and IL-6 as Predictors of Mortality in Cirrhotic Patients with Acute Kidney Injury

Abstract: Background. Acute kidney injury (AKI) affects from 20% to 50% of cirrhotic patients, and the one-month mortality rate is 60%. The main cause of AKI is bacterial infection, which worsens circulatory dysfunction through the release of HMGB1 and IL-6. Objectives. To evaluate HMGB1 and IL-6 as biomarkers of morbidity/mortality. Methods. Prospective, observational study of 25 hospitalised cirrhotic patients with AKI. Clinical and laboratory data were collected at the time of diagnosis of AKI, including serum HMGB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The above-mentioned findings suggested that HMGB1 was mainly secreted by podocytes and maybe partly released by apoptotic podocytes. Previous studies have shown that HMGB1 is a late inflammatory factor and secreted by immune cells and injured cells [ 22 , 23 ]. To investigate the role of HMGB1 in podocytes, HMGB1 expression in podocytes was suppressed by HMGB1 siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned findings suggested that HMGB1 was mainly secreted by podocytes and maybe partly released by apoptotic podocytes. Previous studies have shown that HMGB1 is a late inflammatory factor and secreted by immune cells and injured cells [ 22 , 23 ]. To investigate the role of HMGB1 in podocytes, HMGB1 expression in podocytes was suppressed by HMGB1 siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines such as IL-6 are secreted to a much greater extent in the face of serious injuries or infections that manifest systemically with haemodynamic instability or more important metabolic disorders. In these situations, IL-6 is closely related to shock, multiple organ failure and death [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HMGB1 has been recognized as a danger signal involved in the pathogenesis of various inflammatory diseases, malignancies, and injury [ 57 , 58 , 59 ]. On the contrary to these functional roles, HMGB1 is also useful as a biomarker in various diseases [ 60 , 61 ]. HMGB1 is noticed in serum in patients with severe cutaneous adverse reactions [ 62 , 63 ].…”
Section: Clinical Sign and Biomarker For Drug Eruptionmentioning
confidence: 99%